Pengaruh Serat Sabut Kelapa Terhadap Kuat Tekan dan Kuat Tarik Beton Mutu (f’c 19,3 Mpa) - Benu, Ari ; Ningrum, Diana ; Wijaya, Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Developments in Indonesia in the physical sense like housing and other means, with the increasing population. On the other hand the construction of the House were living with a cheap cost is a program that always have to be coveted by both the Government and the community at this time. In an effort to reduce the cost of the building, one way is with utilization of household waste, as it is easy to obtain, and may be the source of livelihood of the local people of whom the utilization of coir fibers taken. The value of strong press and strong pull from each of the test objects with a different aggregate binder on the value of strong concrete press for 2 cm value strong and powerful to 286.0 press press 4 cm for the value of strong tekan290 .6 for powerful press and to 269.6 6 cm strong tensile concrete 2 cm of strong value for length of pull and 129.6 fiber tensile strong 121.1 rating 4 cm and 6 cm for the strong value of the highest tensile 177.7 data or highest value The addition of coir fibers for concrete mix in testing powerful press and its strong for some cylinders increased for his testing and for some have decreased against testing. For the length of the fiber coir for testing robust press and strong tensile concrete in concrete mix that is a strong value 6 press increased